Cause investigation analysis and experimental argumentation about acidic water in the oil shale open pit of Maoming City. (August 2019) - Zhou, Junguang; Ji, Wang; Sha, Chang; Pan, Chaoyi; Guo, Qingwei; Wang, Jingsong; Cheng, Sili
Abstract: This paper analyzes the sources and causes of the natural history of Maoming city open pit water, combined with the experimental research on the reasons of present continuous mine water acidification, and taking the total mass of H + dissolved in water as an indicator. The results show that the main reason for the continuous acidification of the open pit mine is the accumulation of contaminated soil at random and the leaching of acid from the soil. Acidic substances mainly come from the accumulated waste slag around the pit. In the background of the construction of open-pit mine ecological park, that rain, vegetation restoration, river governance slag pollution is the key to acidic mine water.